Construction of strongly coupled 2D–2D SnS2/CdS S-scheme heterostructures for photocatalytic hydrogen evolution. Issue 5 (8th February 2023) - Chen, Xiaoyu; Han, Zhi; Lu, Zonghao; Qu, Tingting; Liang, Ce; Wang, Yu; Zhang, Bin; Han, Xijiang; Xu, Ping
Abstract : 2D–2D S-scheme SnS2 /CdS heterostructures have been constructed, with close face-to-face contact and strongly coupled interactions to improve the charge transfer kinetics, which exhibit excellent photocatalytic hydrogen evolution activity. Abstract : The fabrication of neoteric photocatalysts with high-efficiency charge separation for the solar-driven hydrogen evolution reaction (HER) remains a challenge. The construction of strongly coupled two-dimensional (2D)–2D heterostructures facilitates charge spatial migration due to the regulation of the interlayer forces and electronic structures. In this work, we demonstrate novel 2D–2D SnS2 /CdS heterostructures by loading SnS2 nanosheets (SnS2 NSs) onto CdS nanosheets (CdS NSs). The SnS2 /CdS heterostructures possess close face-to-face contact and strongly coupled interactions to improve the charge transfer kinetics, and the loading of SnS2 can enhance light absorption and suppress the photocorrosion of CdS. The optimized S-scheme SnS2 /CdS heterostructures exhibit excellent photocatalytic hydrogen evolution activity in lactic acid sacrificial solution under visible light ( λ ≥ 420 nm), affording the highest hydrogen evolution rate on SnS2 /CdS heterostructures with 35 wt% SnS2 (5.18 mmol g −1 h −1 ), which is approximately 6-fold higher than that of pure CdS NSs (0.87 mmol g −1 h −1 ). In addition, a highest apparent quantum efficiency (AQE) of 59.3% was obtained at 420 nm. When methanol was used as the sacrificial agent, the hydrogen production rate reached 3.27 mmol g −1 h −1 and methanol was oxidatively reformed into methoxymethanol (CH3 OCH2 OH). This work provides a feasible method for designing strongly coupled 2D–2D heterostructure photocatalysts for energy storage and conversion applications.